PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN PENGALAMAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA THE BALCONE SUITES & RESORT - Sri Kemala; Fira Olivia Krisanti; Diah Permata; Almasdi Almasdi (Procuratio : Jurnal Ilmiah Manajemen, 2024)
This research aims to see the influence of service quality on customer loyalty and the customer experience as an intervening variable at The Balcone Suites & Resort. This research uses quantitative methods, and then the data is processed and analysed using the Structural Equation Modelling—Partial Least Squares (SEM-PLS) method. The number of research respondents was 110. The results of this research show that (1) there is a positive and significant influence between Tangible and customer loyalty at The Balcone Suites & Resort. (2) There is a negative and insignificant influence between reliability and empathy on customer loyalty at The Balcone Suites & Resort. (3) There is a positive but not significant influence between responsiveness, assurance, and customer loyalty at The Balcone Suites & Resort. (4) There is a positive but not significant influence between tangibility, reliability, responsiveness, assurance, and empathy on the customer experience at The Balcone Suites & Resort. (5) There is a positive and significant influence between customer experience and customer loyalty at The Balcone Suites & Resort. (6) There is a positive and significant influence between Tangible on Customer Loyalty and Customer Experience as an Intervening Variable at The Balcone Suites & Resort. (7) There is a positive but not significant influence between reliability, responsiveness, assurance, and empathy on customer loyalty, with customer experience as an intervening variable at The Balcone Suites & Resort. Penelitian ini bertujuan untuk melihat pengaruh Kualitas Pelayanan terhadap Loyalitas Pelanggan dengan Pengalaman Pelanggan sebagai Variabel Intervening pada The Balcone Suites & Resort. Penelitian ini menggunakan metode kuantitatif, kemudian data diolah dan dianalisis menggunakan metode Structural Equation Modelling – Partial Least Square (SEM-PLS). Responden penelitian berjumlah 110 orang. Hasil penelitian ini menunjukkan bahwa: (1) Terdapat Pengaruh positif dan signifikan antara Tangible terhadap Loyalitas Pelanggan di The Balcone Suites & Resort. (2) Terdapat Pengaruh negatif dan tidak signifikan antara Reliability dan Empathy terhadap Loyalitas Pelanggan di The Balcone Suites & Resort. (3) Terdapat Pengaruh positif tetapi tidak signifikan antara Responsivenes, Assurance, terhadap Loyalitas Pelanggan di The Balcone Suites & Resort. (4) Terdapat Pengaruh positif tetapi tidak signifikan antara Tangible, Reliability, Responsiveness, Assurance, dan Empathy terhadap Pengalaman Pelanggan di The Balcone Suites & Resort. (5) Terdapat Pengaruh positif dan signifikan antara Pengalaman Pelanggan terhadap Loyalitas Pelanggan di The Balcone Suites & Resort. (6) Terdapat Pengaruh positif dan signifikan antara Tangible terhadap Loyalitas Pelanggan dengan Pengalaman Pelanggan sebagai Variabel Intervening di The Balcone Suites & Resort. (7) Terdapat Pengaruh positif tetapi tidak signifikan antara Reliability, Responsiveness, Assurance, dan Empathy terhadap Loyalitas Pelanggan dengan Pengalaman Pelanggan sebagai Variabel Intervening di The Balcone Suites & Resort.